PENGARUH PENDIDIKAN KESEHATAN TERHADAP PERILAKU HIDUP BERSIH DAN SEHAT PADA PEMULUNG DI TPA WONOKROMO-SURABAYA - Dewi, Erika Untari (S1 Keperawatan, 2015)
Essentially, health education is a wish or an effort to deliver health message to society, group or individual in order to improve healthy lifestyle behaviors. Aim of this research is to know influence of health education to healthy lifestyle behaviors on scavengers at TPA Wonokromo Surabaya. This research used pre experiment design by using one group pre-post test design. Population of the research was 20 respondents who are scavengers at TPA Wonokromo Surabaya. 19 of 20 respondents were sampled using simple random sampling. Data collection used questionnaire before and after participating in health education about healthy lifestyle behaviors. Then the data was tested using wilcoxon test. Result of the research indicated that most respondents have less behavior (11 or 57.89%) before participating in health education and after participating in health education there are 14 or 73.86% who have good behavior and statistical result indicated that p = 0.000. It means there is influence of health education to healthy lifestyle behaviors on scavengers at TPA. Wonokromo Surabaya. Therefore, health education on healthy lifestyle behavior can be enhanced to make good healthy lifestyle behaviors. Keywords: health education, healthy lifestyle behavior